MULTI UPPER LIMB EXERCISE (MUL-eX) LATEST INNOVATION BY HOSPITAL USM RECOVERY UNIT - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, August 2015 Realising that the use of available exercise equipment for the rehabilitation of patients recovering from arthritis, sports injuries, stroke and fracture can be quite burdensome, the Beyond Rehab group of the Rehabilitation Unit, Hospital Universiti Sains Malaysia (HUSM) has taken the opportunity to produce an innovative project known as the 'Multi Upper Limb Exercise' (MULeX).